Composition en couleur avec LaTeX - Goossens, M; Rahtz, S (GUTenberg association, 1994)
In this article we show some basic principles underlying the use of colour. After explaining how colour is reproduced in printers, we show one implementation with LaTeX of using it in your work and give a few examples of colour use. We also explain how to make simple colour separations using PostScript and dvips.